Locally-produced chicken litter biochar as substitute fertilizer in promoting Amaranthus viridis L. growth in tropical soil - Md Yusof, Md Rozaidi (2019)
Environmental pollution from chemical fertilizers and healthy food awareness have created an interest in the use of organic fertilizer in agriculture. Biochar is highly recommended in agriculture as a substitute for chemical fertilizers, as biochar applications can enhance soil and crop productivity. Thus, the objectives of this study were to determine: (i) appropriate method for producing biochar from chicken litter; (ii) the effects of biochar application on growth and yield of Amaranthus viridis (Spinach); (iii) the effects of biochar on selected soil physical and chemical properties; and (iv) the cost-effectiveness of using biochar as organic fertilizer in the cultivation of Amaranthus viridis. In this study, local chicken litter biochar (LCLB) was produced using clay pots, and the concept of self-combustion was used without efficient oxygen control in the clay pots. The chicken litter was dried for a week before being combusted in the clay pots for nine hours. The biochar was collected and sieved by using 2 mm sieve to separate the ash from biochar, and finally, the biochar was ground using Retsch Cutting Mill to get a fine grade of biochar. Scanning Electron Microscopy (SEM) attached to Energy Dispersive X-Ray (SEM-EDX JEOL JSM-6400) was used to determine surface morphology and elemental composition of the biochar. Standard procedures were also used to determine the selected chemical properties of the biochar. The selected chemical properties of the LCLB were compared with those of a commercial chicken litter biochar (CLB) from Black Earth, Australia (as a standard). Both biochars were high in pH due to their alkaline organic functional groups such as carboxyl, phenol, and alcohol, which were deprotonated to the conjugate base. The total organic C of CLB was 10.5% higher than that of LCLB. The CEC of the CLB and LCLB were 80.51 ± 0.12 and 75.45 ± 0.17 cmol kg−1, respectively. Total N of the two biochars were low due to the gasification of N during combustion. Total K of the two biochars were high, indicating that, they are the ideal source for K. Phosphorous, Zn, and Cu contents of LCLB were higher than those of CLB. Field assessment of the biochars for two cropping trials of Amaranthus viridis showed that they improved soil pH, EC, P, K, Ca, and Mg. In the first planting cycle, LCLB and CLB improved nutrient uptake. In the first field trial, the plots with CLB at five tons ha-1 showed the highest yield (13.44 tons ha-1), followed by six tons ha-1 of CLB with a yield of 12.68 tons ha-1, and four tons ha-1 of CLB with a yield of 12.11 tons ha-1. In contrast, at five, six, and four tons ha-1 of LCLB, the yields of Amaranthus viridis were 12.33, 11.73, and 11.32 tons ha-1, respectively. These results revealed that five tons ha-1 of CLB and LCLB produced the optimum yield of Amaranthus viridis as the yields of the two at five tons ha-1 were significantly higher than the existing chemical fertilization. However, heavy rainfall and flood during the second planting season decreased the effectiveness of the biochars in improving the yield of Amaranthus viridis due to nutrient losses through runoff and leaching. Economic viability for using the biochars in Amaranthus viridis cultivation showed that the use of LCLB is economically viable, based on the B/C ratio of 10.98 indicates that every RM 1 invested will yield a capital return of RM 9.98 with a net profit of RM 171,774.15 per ha greater than the net earnings for CLB (RM 64,326.15) and inorganic fertilization (RM 39,157.65). The findings of this study suggest that locally produced chicken litter biochar (LCLB) can be used to improve soil productivity and the economic yield of Amaranthus viridis. Five tons ha-1 of LCLB is the optimum rate for optimum yield. The implication of this is that LCLB can be used to replace inorganic fertilization in Amaranthus viridis cultivation, and it can promote the growth of the plant as good as imported biochar and thus will provide the farmer with higher net profit. Several trials could be carried out to consolidate the findings of this present study.